Physical mapping of a low-copy DNA sequence in rye (Secale cereale L.). - Gustafson, J P (1990)
A 900-base-pair (bp) sequence from a cDNA clone of the rye endosperm-storage-protein gene Sec-1 was labeled with biotin and hybridized to Secale cereale 'Blanco' chromosomes. Hybridization was seen on the satellite part of the short arm of chromosome 1R, where the Sec-1 gene has been genetically mapped, in approximately 8.5% of the cells analyzed. The clone cross-hybridized at a lower frequency to rye chromosome arms 1R (long) (4.4%) and 2R (short) (2.6%), where two additional rye storage-protein loci, Sec-3 and Sec-2, respectively, have been mapped. A fourth hybridization site was observed on the short arm of chromosome 6R at a frequency of 3.0%. The cross-hybridization is attributed to a combination of residual sequence homology between the protein loci and the low-stringency conditions used in in situ hybridization. In situ hybridization mapping, in combination with chromosome walking by using molecular techniques, is suggested as an excellent approach to physical mapping of chromosomes.